2020
DOI: 10.1177/0033294120967276
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Environmental Manifestation of Types of Music on Reinforcing Mindfulness and Concurrent Calorie Intake

Abstract: Background The role of music on energy intake is conflicting, and recent research has suggested a positive association between classical music listening and mindfulness. Objective The purpose of the present study was to investigate the effect of music, specifically classical music on state mindfulness and calorie intake of energy-dense foods. Method One hundred participants were randomly assigned to either a classical, popular or no music condition, and were served a variety of sweet (i.e., chocolate and cooki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…It has also been demonstrated that different types of music distinctly impact the relationship between music and food intake. For example, rock music has correlated with increased consumption of alcohol [ 36 ], while classical music appears to help reduce the intake of savory foods [ 37 ]. People also tend to spend more money at a restaurant when classical or jazz music is playing rather than pop music or no music at all [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that different types of music distinctly impact the relationship between music and food intake. For example, rock music has correlated with increased consumption of alcohol [ 36 ], while classical music appears to help reduce the intake of savory foods [ 37 ]. People also tend to spend more money at a restaurant when classical or jazz music is playing rather than pop music or no music at all [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Music could thus certainly offer highly effective and pleasurable tools to further promote well-being and health (Vuilleumier and Trost, 2015 ; Lynch and Wilson, 2017 ; Sorensen et al, 2018 ; Menninghaus et al, 2019 ). In the future, in-depth research on the effects of mindfulness meditation training on aesthetic emotion will be conducive to a better understanding of the functioning and cultivation of a healthy mind (Hölzel et al, 2011b ; Bueno et al, 2015 ; Loo et al, 2020 ; Misba et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It includes two components, namely, regulating the attention of an individual to maintain the immediate experience and approaching the experiences of an individual with curiosity, openness, and acceptance (Lei et al, 2016). The nonjudgment and openness experience induced by state mindfulness meditation are highly related to body awareness (Brown and Ryan, 2003;Diaz, 2013;Rodríguez-Carvajal and Lecuona, 2014;Clark et al, 2015;Anderson, 2016;Loo et al, 2020;Misba et al, 2020). Temporary mindfulness meditation training, as a relaxed state of enhanced self-regulation, effectively induces the openness of individuals to experience and non-judging of inner experience by individuals, thereby improving emotion processing (Bishop, 2004;Tan et al, 2014;Bueno et al, 2015;Lei et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations